Exergame-Driven High-Intensity Interval Training in Untrained Community Dwelling Older Adults: A Formative One Group Quasi- Experimental Feasibility Trial - Rebsamen, Stefanie; Knols, Ruud H.; Pfister, Pierrette Baschung; de Bruin, Eling D. (Frontiers in Physiology, 2019)
Purpose To investigate the feasibility of an exergame-driven high-intensity interval training (HIIT) and its effects on cardiovascular fitness in untrained community dwelling older adults. Methods Twelve older participants [10 women, age 72.3 (SD: 4.44) years] performed a high-intensity interval exergame intervention three times a week for 4 weeks. Data was acquired during two baseline and one final measurement. Feasibility outcomes included attrition, adherence, acceptability [Technology Acceptance Model Questionnaire (TAM)], usability [System Usability Scale (SUS)], and enjoyment of exergaming. Furthermore, participants’ physical activity levels pre and post intervention were compared to physical activity levels for similar types of training. The secondary outcome was exercise capacity [heart rate at rest (HRrest), heart rate variability (HRV), maximum heart rate (HRmax), and maximum workload (W, in watt)] evaluated through maximal exercise testing. Results Eleven participants completed the study (8% attrition), without any adverse events. Adherence to the HIIT intervention was 91% and participants showed high acceptance of the intervention with TAM scores between 5.8 and 6.7 points. User satisfaction was rated as excellent (SUS total score: 93.5 of 100) and the overall enjoyment of exergaming scored 4.5 of 5 possible points. Total exercise time ranged from 19 to 35 min with a mean of 30.8 (SD: 3.6) min. Actual high-intensity exercise time showed consistency with the target exercise time in 98% percent of trainings. Eighty-six percent of high-intensity intervals met the targeted intensity range (>70–90% of HRmax). Thirty-six percent of the recovery periods were completed with a heart rate above the target range of 50–70% of HRmax. Maximum workload (W) during the incremental exercise test post-training increased significantly compared to the baseline measurements one and two (p = 0.032, effect size r = 0.77 and p = 0.012, r = 0.87). Conclusion High-intensity interval training through exergaming is feasible, safe, and shows high usability and acceptance in community dwelling older people. Exergame-driven HIIT had a significant effect on maximum power output on an incremental exercise test. A more extensive exergame intervention period, higher work to recovery ratios as well as a higher-intensity activity should be considered in future projects.